Characterization of the epidemiological profile and morbimortality caused by Congenital Syphilis in the municipality of Blumenau – Santa Catarina from 2015 to 2021 (Research, Society and Development, 2022)
Objective: To analyze the epidemiological profile of the cases of Congenital Syphilis reported in Blumenau - Santa Catarina, as well as investigate the sociodemographic and clinical aspects between the years 2015 and 2021. Methodology: This is a descriptive, analytical, cross-sectional and retrospective study, with a quantitative approach. Data were obtained through the Information System of Notifiable Diseases, Mortality Information System, by the Epidemiological Surveillance Directorate and the Basic Data Indicators of Syphilis in Brazilian municipalities. Results: 515 cases of Congenital Syphilis and Gestational Syphilis were notified in the period studied, presenting a successive sequence, with a reduction of the subsequent cases in 2022 and growth of 335% in the following year (average incidence of 3.6 cases/1,000 live births). According to the data analyzed 57.6% of pregnant women were aged between 20 and 29 years, with low educational level and white, 91% of pregnant women had prenatal care, 71.1% were diagnosed with syphilis during prenatal care, of which 98.2% had inadequate treatment or no treatment. It was observed that 98.2% of infected neonates were less than seven days old and were diagnosed with recent Congenital Syphilis. Conclusion: The growing incidence of CS reported in Brazil and in Blumenau, in the period studied determines the need for training of health professionals in the realization of prenatal care for adequate assistance and effective monitoring during the gestational period.